Pendekatan Bermain Sebagai Metode Pembelajaran Efektif Untuk Meningkatkan Teknik Lari Jarak Pendek Di SDN Perak Barat VI Surabaya - Rr. Sri Setiorini (Educational Research Center, 2025)
This study aimed to evaluate the effectiveness of an interactive and engaging teaching approach for the 50-meter sprint technique among Grade V students at SDN Perak Barat VI Surabaya for the 2018/2019 academic year. Implemented as a Classroom Action Research (CAR), this study was conducted in two cycles, each involving planning, action, observation, and reflection phases. The initial observations showed that many students lacked understanding and skill in executing the 50-meter sprint technique. This led to the development and application of a revised teaching strategy in Cycle 2, incorporating feedback from observers and peers to enhance learning outcomes. The results of Cycle 2 indicated a significant improvement in students' knowledge, skills, and attitudes towards the sprint technique. All 32 students, or 100%, demonstrated mastery in performing the 50-meter sprint correctly, achieving full competence. Additionally, observations by peers and observers noted that the learning process was highly engaging, with students displaying enthusiasm, active participation, and positive attitudes, such as sportsmanship, discipline, confidence, and motivation. These results represent a substantial improvement from Cycle 1, demonstrating the success of the revised teaching approach. This study concludes that an interactive and student-centered learning method significantly enhances cognitive, psychomotor, and affective aspects of students' learning outcomes. It emphasizes the importance of adaptive teaching methods tailored to students' needs to achieve optimal learning results. The findings of this study are expected to serve as a reference for educators in developing more dynamic and effective teaching strategies to improve the overall quality of education, particularly in Physical Education, Sports, and Health